(untitled) (Eurasian Journal of Philology Science and Education, 2025)
The study addresses the critical need to integrate pragmatics into teaching the Kazakh language to develop student’s communication skills in a globalized and multicultural context. The research explores strategies for preparing future teachers to effectively teach pragmatics, a key yet often overlooked component of language education. The study adopts a qualitative thematic analysis of over 60 academic works, focusing on the pedagogical challenges, instructional methods, and assessment strategies for teaching pragmatics. Comparative analysis between English and Kazakh language pragmatics highlights transferable methods while accounting for cultural and linguistic differences. Key findings underscore the abstract and culturally embedded nature of pragmatics, the lack of resources for Kazakh language instruction, and the importance of clear and explicit teaching methods. The study emphasizes the role of innovative tools, including digital platforms, in enhancing pragmatic competence. It contributes to the field by proposing actionable recommendations for teacher training programs, curriculum development, and pragmatic assessment tools tailored to the Kazakh context. The results offer practical insights for language educators and policymakers, fostering cross-cultural communication and effective language teaching in a rapidly changing world. Key words: pragmatics, teacher training, challenges of teaching, pragmatic competence.